Changes During the Processing of Duck Meatballs Using Different Fillers after the Preheating and Heating Process - Putra, A.A.; Huda , N.; Ahmad, R. (International Journal of Poultry Science, 2010)
In the process of manufacturing duck meatballs, three different fillers (corn, sago and cassava) are used as representatives of grain, root and palm sources of fillers. Different stages of duck meatball processing, such as dough, pre-heating and heating, were analyzed to further the research on the manufacturing process of duck meatballs. In this study, the nutritional contents, physicochemical characteristics and sensory attributes are collected. In general, there were no significant differences (p>0.05) among the fillers in the characteristics that we examined. However, there were significant differences (p<0.05) among the different stages of the processing. After preheating and heating, the moisture contents were significantly increased (p<0.05) and the increase in moisture content directly caused other nutrient components to decrease. The pH, lightness, texture, cooking yield, moisture retention, diameter and folding test results were increased (p<0.05) after the preheating and heating stages. Cassava treatment showed a significant higher (p<0.05) in the terms of aroma of the final products meanwhile other sensory attributes were not significantly different (p>0.05). Sensory evaluation for overall acceptability showed that all treatments were acceptable.